2017
DOI: 10.2320/matertrans.m2016356
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Wear Resistance of Zr-Based Bulk Metallic Glass by Thermal Oxidation Treatment

Abstract: Enhancement of surface properties such as wear resistance of Zr-based bulk metallic glasses (BMGs) is important for many applications of the materials. In this paper, the effect of thermal oxidation on the tribological behavior of a Zr-Ti-Cu-Al-Y BMG was studied. It is found that oxidation treatment greatly improves the wear resistance of the BMG, which is ascribed to the formation of a layer of oxidized scale. This result is bene cial for the improvement of surface properties and further application of the Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Haratin et al [23] shown improved surface hardness of (Zr 55 Cu 30 Al 10 Ni 5 ) 98 Er 2 BMG from~600 to~1200HV using gaseous oxidising treatment, in which case a topmost Cu-rich zone formed on the surface oxide. Zhou and co-researchers [24] reported improved wear resistance of Ni-free (Zr 0.5 Ti 0.02 Cu 0.38 Al 0.1 ) 98 Y 2 BMG by thermal oxidation treatment below the glass transition temperature (T g ) of the BMG.…”
Section: Potential Solutions Limitations and Research Aimmentioning
confidence: 99%
“…Haratin et al [23] shown improved surface hardness of (Zr 55 Cu 30 Al 10 Ni 5 ) 98 Er 2 BMG from~600 to~1200HV using gaseous oxidising treatment, in which case a topmost Cu-rich zone formed on the surface oxide. Zhou and co-researchers [24] reported improved wear resistance of Ni-free (Zr 0.5 Ti 0.02 Cu 0.38 Al 0.1 ) 98 Y 2 BMG by thermal oxidation treatment below the glass transition temperature (T g ) of the BMG.…”
Section: Potential Solutions Limitations and Research Aimmentioning
confidence: 99%
“…Metallic glasses (MGs), which are newcomers to the eld of amorphous materials, have attracted great interests due to their remarkable mechanical, physical, and chemical properties [1][2][3] . Their disordered atomic structures inherited from molten melts generate ultrahigh strengths, high elastic limits, low Young s moduli, good wear resistances, and excellent corrosion resistances, leading to comprehensive application potentials as structural and functional materials [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%